Med1 controls CD8 T cell maintenance through IL‐7R‐mediated cell survival signalling. Issue 10 (17th March 2021) - Lei, Lei; Yang, Xiaofeng; Su, Yanhong; Zheng, Huiqiang; Liu, Jun; Liu, Haiyan; Zou, Yujing; Jiao, Anjun; Wang, Xin; Zhang, Cangang; Zhang, Xingzhe; Zhang, Jiahui; et al.
Abstract: Under steady‐state conditions, the pool size of peripheral CD8 + T cells is maintained through turnover and survival. Beyond TCR and IL‐7R signals, the underlying mechanisms are less well understood. In the present study, we found a significant reduction of CD8 + T cell proportion in spleens but not in thymi of mice with T cell‐specific deletion of Mediator Subunit 1 (Med1). A competitive transfer of wild‐type (WT) and Med1‐deficient CD8 + T cells reproduced the phenotype in the same recipients and confirmed intrinsic role of Med1. Furthermore, we observed a comparable degree of migration and proliferation but a significant increase of cell death in Med1‐deficient CD8 + T cells compared with WT counterparts. Finally, Med1‐deficient CD8 + T cells exhibited a decreased expression of interleukin‐7 receptor α (IL‐7Rα), down‐regulation of phosphorylated‐STAT5 (pSTAT5) and Bim up‐regulation. Collectively, our study reveals a novel role of Med1 in the maintenance of CD8 + T cells through IL‐7Rα/STAT5 pathway‐mediated cell survival.